AKUISISI DATA SINYAL ECG DAN PULSE OXSIMETRY ( SPO2 ) MENGGUNAKAN BIOMEDICAL MEASUREMENT KL.710 - Sumber .; Abd Kholiq (JURNAL PENELITIAN KESEHATAN, 2016)
The development of medical technology as we know has spread rapidly. Hence, the systemfor serving people get better and more profesional. Heart disease took first place of the motdangerous disease. More than 30% of total mass of the world invected in 2008. ECG signals andSpO2 using biomedical measurement KL-710, KL-710 setted on sampling frequency on 1000Hz.With the value beat per minute of ECG signals and SpO2 no more than 120 peak per minute, sothe sampling frequency on 1000 Hz might be enough to get the leads signals that needed. Adultmen show us the average of electrocardiogram period is 1 second. This period decrease 0.06second than adult woman’s period of electrocardiogram on 0.94 second. With this decresing pointof period ( men’s and woman’s ) the value of SpO2 peaks has no friction yet. So the value of beatper minute for the measurement of electrocardiogram shifting on 4. This caused by the rithm ofSpO2, though theoriticaly its peak equal to beat per minute but actually there is defferences fromtwo to three peaks per minute